LOW VP/VS RATIOS IN THE CRUST AND UPPER MANTLE BENEATH THE SEA OF OKHOTSK INFERRED FROM TELESEISMIC PMP, SMP, AND SMS UNDERSIDE REFLECTIONS FROM THE MOHO - Zheng Y.; Lay T. (My University, 2006)
Teleseismic ground motion recordings of deep earthquakes often contain clear seismic wave reflections from the free surface above the source (pP, sP, sS), with isolated precursors (pMP, sMP, and sMS) produced by underside reflections from the Moho (the crust-mantle boundary) below the free surface reflection points. The waveforms of the depth phases and their precursors are readily modeled, providing constraints, for steep angles of incidence, on integrated two-way crustal travel times and Moho shear and compressional impedance contrasts above deep earthquake source regions. We model surface reflection waveforms in stacks of three-component, long-period WWSSN and digital broadband seismograms for signals traversing the crust and upper mantle beneath the Sea of Okhotsk, which overlies deep earthquakes in the subducted Kurile slab. The crust beneath most of the Sea of Okhotsk is 19-25 km thick, indicating a submerged continental margin, with minor crustal thinning toward the Kuril back-arc basin, where thin oceanic crust is found. Modeling pMP and sMS phases that sample the same subregion provides tight constraints on the Vp/Vs ratio in the crust and uppermost mantle (assuming common density structure and consistent crustal thickness for P and S waves); the absolute velocities are not constrained by the data. We find unusually low Vp/Vs ratios in the range 1.6-1.7 for the uppermost mantle under the Sea of Okhotsk and comparably low average Vp/Vs ratios for the crust in several regions. The presence of fluids and extensive silica enrichment, possibly involving low-temperature veining, are viable explanations for the anomalous Vp/Vs ratios; this may represent an important process of continentalization taking place landward from the volcanic arc in subduction zones. Copyright 2006 by the American Geophysical Union.